(untitled) (The Pakistan Development Review, 1988)
The quantification of landlessness is a formidable task. Conceptual ambiguities involved in the classification of landlessness and data limitations compound the difficulties in the estimation. Landlessness, which is an elusive concept, tends to acquire interpretations which vary with the objectives, context and estimation procedures adopted in different research endeavours. The denotation and connotation of the concept of landlessness, the population of interest (or at risk) and the objectives of measurement therefore need to be spell out very clearly for a meaningful and policy-relevant exercise. Identification of the state of landlessness using the criterion of ownership and access to land, has often been made. While the ’ownership’ may be clear in certain contexts, that of ’access’ needs further explanations in terms of the nature, extent and type of access. A related question, is the demarcation of the population or its subset whose landlessness is to be estimated: are all the inhabitants of an area or the ones who primarily depend on land for their livelihood be regarded as the relevant population. The dependence on land needs to be further specified whether the person is engaged in agricultural operations as worker or not.